Antithymocyte globulin induction therapy improves survival in lung transplantation for cystic fibrosis. (12th November 2012) - Jaksch, Peter; Wiedemann, Dominik; Augustin, Victoria; Muraközy, Gabriela; Scheed, Axel; Kocher, Alfred A.; Klepetko, Walter
Summary Cystic fibrosis (CF) is an inherited condition that leads to respiratory failure and is the third most common indication for adult bilateral lung transplantation (LuTX). In contrast to other lung diseases, the immune system of CF patients is up‐regulated and we therefore hypothesized that these patients would benefit from induction therapy. In the current study, we investigated the impact of antithymocyte globulin (ATG) induction therapy in CF patients after LuTX. One hundred and forty six patients who underwent LuTX for CF at our centre between January 1999 and December 2010 were included in the study and retrospectively analysed. They were divided into two groups according to the immunosuppressive protocol: group‐A (n = 103) with and group‐B (n = 43) without induction therapy on top of the basic calcineurin inhibitor based triple immunosuppression with mycophenolate mofetil and steroids. Perioperative survival was significantly better in the ATG group, a benefit sustained for the entire follow‐up. ATG induction resulted in a significantly lower incidence of acute rejections without an increase in infectious complications. Taken together, our results indicate that ATG induction therapy confers a significant survival benefit in CF patients undergoing LuTX and reduces rejection. We advocate the use of induction therapy in this patient cohort.